IMPACT OF WORKFORCE DIVERSITY ON CREATIVITY AND INNOVATION ON MULTINATIONAL CORPORATION IN NIGERIA - Muhammed Olowookere (Research In Management and Accounting (RIMA), 2026)
This study aims to examine the impact of workforce diversity on the creativity and innovation of MNCs in Nigeria. This research specifically examines how cognitive, ethnic, and gender diversity influences innovative outcomes in MNCs. A descriptive research design was employed using a quantitative approach. The population of the study were 675 permanent staff of Olam Group of Company in Nigeria. A sample size of 246 participants was determined using the Krejcie and Morgan formula. Data was gathered through structured questionnaires distributed to 675 permanent employees of the Olam Group. The analysis utilized Structural Equation Modeling (SEM), revealing that cognitive diversity has a strong effect on creativity and innovation, with an original sample value of 0.385, a T-statistic of 11.372, and a p-value of 0.000. Ethnic diversity demonstrated a positive impact with an original sample value of 0.208, T-statistic of 5.067, and p-value of 0.000. Gender diversity emerged as the most significant contributor, with an original sample value of 0.509 and a T-statistic of 13.222, also yielding a p-value of 0.000. The R-Square value of 0.845 indicates that 84.5% of the variance in creativity and innovation is explained by the model incorporating these diversity dimensions. The findings highlight that workforce diversity plays in enhancing creativity and driving innovation in Multinational Corporation. Recommendations include promoting diverse hiring practices, fostering an inclusive culture, and ensuring equitable representation across gender and ethnic lines.